Optimalisasi Manajemen Logistik Rumah Sakit untuk Meningkatkan Efisiensi Pengadaan dan Distribusi Obat di Era Digital - Laksono, Adi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
MEffective logistics management plays a crucial role in ensuring the availability, continuity, and efficiency of drug procurement and distribution in hospitals. In the digital era, transforming logistics systems has become a strategic necessity to address challenges such as limited resources, distribution delays, and stock mismatches. This study aims to analyze optimization strategies for hospital logistics management through the utilization of digital technology to enhance the efficiency of drug procurement and distribution. Using a qualitative approach through literature studies and analysis of recent scientific publications, this research explores the implementation of technologies such as Hospital Management Information Systems (HMIS), barcode tracking, the Internet of Things (IoT), and big data analytics in pharmaceutical logistics processes. The findings reveal that digitalization of logistics can improve supply chain transparency, stock accuracy, cost control, and decision-making speed. Nevertheless, challenges such as infrastructure readiness, resistance to change, and limited human resources remain significant barriers to implementation. Therefore, supportive policies, continuous training, and comprehensive system integration are needed to realize efficient, adaptive, and sustainable in the digital era